Two new species, transference, notes, and new record in South American Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) - Vlasak, Josef; Santos-Silva, Antonio; Nascimento, Francisco Eriberto De L. (Zootaxa, 2020)
Two new species are described from Ecuador: Anisopodus flavomarginatus, and Leptocometes brevicornis. Hyperplatys argus (Bates, 1872) is transferred to its original genus: Anisopodus White, 1855. Comments regarding the type locality of Hylettus eremita (Erichson, 1847) and variation of pronotal and elytral pubescence pattern in the species are provided. The species is reported from Colombia for the first time. The type locality, number of specimens in the original description, and institution depositary of the syntypes of Astynomus sallei Candèze (1861 (= H. eremita) are discussed.